2019
DOI: 10.3389/fncel.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Phosphorylation Is Essential for Axonal Growth of Human Neurons Derived From iPSCs

Abstract: Proper axonal growth and guidance is essential for neuron differentiation and development. Abnormal neuronal development due to genetic or epigenetic influences can contribute to neurological and mental disorders such as Down syndrome, Rett syndrome, and autism. Identification of the molecular targets that promote proper neuronal growth and differentiation may restore structural and functional neuroplasticity, thus improving functional performance in neurodevelopmental disorders. Using differentiated human neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Further it was suggested that Cav1 activates RhoA by inactivation of Src: tyrosine (Y14) phosphorylated Cav1 binds to and activates Csk, which subsequently phosphorylates and inactivates Src in a negative feedback loop 43,52,53 . Similar mechanisms are likely also acting in axonal development as inhibition of Cav1 Y14 phosphorylation inhibited Rac1/Cdc42-mediated axonal growth in human neurons derived from induced pluripotent stem cells 54 . It is currently unclear how Cav1L affects Rho GTPases in Xenopus motor neurons, however, in respect to the studies on isolated neurons, a mechanism affecting the activity of these GTPases seems likely.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further it was suggested that Cav1 activates RhoA by inactivation of Src: tyrosine (Y14) phosphorylated Cav1 binds to and activates Csk, which subsequently phosphorylates and inactivates Src in a negative feedback loop 43,52,53 . Similar mechanisms are likely also acting in axonal development as inhibition of Cav1 Y14 phosphorylation inhibited Rac1/Cdc42-mediated axonal growth in human neurons derived from induced pluripotent stem cells 54 . It is currently unclear how Cav1L affects Rho GTPases in Xenopus motor neurons, however, in respect to the studies on isolated neurons, a mechanism affecting the activity of these GTPases seems likely.…”
Section: Discussionmentioning
confidence: 94%
“…It remains unclear if Xenopus Cav1L morphants would also show neurodegenerative defects, as our Morpholino-mediated approach allowed us only to analyze its role in early neurodevelopment. In vivo as well as overexpression studies of mouse and human hippocampal cell cultures have shown that Cav1 positively regulates neuronal plasticity and neuronal intracellular signaling by recruiting neurotransmitters and neurotrophic factors to synaptic membrane lipid rafts 54 57 . Membrane lipid rafts are especially important for pro-survival and pro-growth receptor signaling in neuronal cells, since receptors and proteins required for synaptic communication mainly localize in these membrane domains 58 .…”
Section: Discussionmentioning
confidence: 99%
“…5B). Both Src activation [76,81] and Src binding to FAK [77] increase in stiffer matrices and could impact the FAK-mediated regulation of pY14Cav1 across changing matrix stiffness. c-Abl also possesses intrinsic mechanosensitivity, its activity significantly increased in cells exposed to hypo-osmotic swelling, on stiff substrates and on mechanical stretching [82].…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, this pathway is induced by nutrient deprivation, but whether similar is used by neurons remains to be Accepted Article determined. Cav1, the component of the caveolin-mediated endocytosis, promotes both immature neurite pruning and leading process elongation through the endocytosis of Ncadherin and L1 cell adhesion molecules [217], while its loss-of-function in Xenopus and/or iPSCs-derived human neurons results in altered axonal outgrowth [218,219]. Interestingly, a recent report suggests that axonal extensions of embryonic hippocampal neurons in a 3D environment are driven by microtubule polymerization and do not require adhesions and/or actin involvement [220].…”
Section: Accepted Articlementioning
confidence: 99%